Design novel structure of high-voltage MOSFET with double trench gates. (October 2019) - Yang, Hong-Jin; Jin, Tao; Feng, Quan-Yuan
Abstract: A new type power MOSFET (Metal Oxide Semiconductor Field Effect Transistor) is designed to reduce the on-resistance and increase the breakdown voltage. The novel structure with double trench gates reduces the JFET annealing process in the process flow and adds only one mask. The Sentaurus TCAD tools are utilized to simulate the fabrication process and electrical characteristics of the proposed structure with a blocking capability of 650 V. The numerical results show that the specific on-resistance of the novel device is reduced by 28.5% compared with that of the traditional one. Also, the reverse breakdown voltage is increased by 3.3%.